Skull Stripping Using Pixel Affinity Graph Method for MRI Head Scans - Shankar, R.Siva; Somasundaram, K. (International Journal of Engineering and Technology, 2018)
Skull stripping from Magnetic Resonance Image (MRI) of human head scan gives strong impact in clinical diagnosis. The Pixel affinity graph method is used as preprocessing technique, and it is applied on adjacent pixels in each row and column of the middle slice of MRI volume. By grouping the subsets through affinity on intensity found in pixels on the graph (PAG), we can locate the large connected brain portion as subset in the image. After the region of interest is located, Skull is stripped and brain portion is segmented. The proposed PAG based algorithm is validated by comparing the results obtained by the popular automated skull stripping method, Brain Extraction Tool (BET). The qualitative and quantitative results show that the proposed algorithm giving better results.